Re-interpretasi Teks Al-Qur’an dalam Budaya Patriarkhi Telisik Epistemologi Feminis Egaliterianisme Asma Barlas - Yusdani Yusdani; Januariansyah Arfaizar (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2022)
The article below explains that women have succeeded in occupying a number of strategic positions and have been successful both in government and other public positions. This proves that the classical view that women are always left behind in all aspects of men cannot be defended anymore. This information clearly shows that women can compete in various political, social, economic, and other fields. However, until now, there is still the view that women are regarded as second-class citizens, inferior, weak, and emotional. Starting from the problems and views that position women who are creatures of the same class as men. This view is caused by the interpretation bias of the commentators towards religious and cultural texts that have been rooted in society. Therefore, building a cultured society based on the values ​​of justice and equality must begin with a re-interpretation of the text of the Qur'an and Hadis accompanied by maximum socialization efforts to change the negative paradigm of society towards women through a number of government policies to encourage the active role of women.